2008
DOI: 10.1088/0953-8984/20/21/215207
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order in perovskite-related SrFeO2F

Abstract: Perovskite-related strontium orthoferrite, SrFeO3−δ, has been fluorinated by a low temperature reaction with poly(vinylidene fluoride) to give the compound SrFeO2F. X-ray powder diffraction shows that fluorination leads to an expansion of the unit cell which is consistent with partial replacement of oxygen by fluorine and consequent reduction in the oxidation state of iron. Magnetometry experiments in the temperature range 10–400 K showed small aligned moments (0.003 ± 0.000 05 μB per Fe3+ ion at 2 T and 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 10 publications
6
60
2
Order By: Relevance
“…The variation of the average magnetic hyperfine field with increasing temperature is shown in Figure 6 and, from Figure 6 about here these data, a magnetic ordering temperature for BaFeO 2 F of 645 ± 5K can be deduced. This is lower than the magnetic ordering temperature of 685 ± 5 K which was previously found for SrFeO 2 F [5]. The variation of the average magnetic hyperfine field with increasing temperature is also compared in Figure 6 with that calculated from the Table 5.…”
Section: Mössbauer Spectroscopymentioning
confidence: 64%
See 1 more Smart Citation
“…The variation of the average magnetic hyperfine field with increasing temperature is shown in Figure 6 and, from Figure 6 about here these data, a magnetic ordering temperature for BaFeO 2 F of 645 ± 5K can be deduced. This is lower than the magnetic ordering temperature of 685 ± 5 K which was previously found for SrFeO 2 F [5]. The variation of the average magnetic hyperfine field with increasing temperature is also compared in Figure 6 with that calculated from the Table 5.…”
Section: Mössbauer Spectroscopymentioning
confidence: 64%
“…We have recently reported [4,5] on the fluorination of oxygen-deficient perovskiterelated SrFeO 3-δ to give a compound of composition SrFeO 2 F with a cubic unit cell and have formulated a model related to the pattern of substitution by fluorine on the octahedral arrangement of oxygen sites around iron in which SrFeO 2 F undergoes a magnetic transition around 300K from a low temperature state with random spin directions to an antiferromagnetic state. We have also prepared the related cubic phase of composition BaFeO 2 F and, in a preliminary neutron powder diffraction study, found it to exhibit G-type antiferromagnetic order at 298K [6].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigations [8] of SrFeO2F by magnetometry in the temperature range 10−400 K showed small aligned moments indicating the absence of ferro-or ferrimagnetism and the separation of field cooled and zero field cooled magnetisations at temperatures around 300 K. The 57 Fe Mössbauer spectra recorded between 80 and 700 K are shown in Figure 2. The spectra recorded between 285 and 650 K showed clear splitting of all the lines contributing to the sextet pattern and showed increasing line-widths and decreasing magnitudes of magnetic hyperfine field until, at 700 K, the magnetic field collapsed to a quadrupole split absorption indicative of the paramagnetic state.…”
Section: Srfeo2fmentioning
confidence: 95%
“…Our initial work [7,8] in synthesising and characterising fluorinated cubic perovskite-related oxides used poly(vinylidene fluoride) for the fluorination of the oxygen deficient phase SrFeO3-d which, because of oxygen deficiency, distorts to an orthorhombic unit cell. The AMO3 unit cell, depicted in Figure 1 (n = infinity), contains strontium (green spheres) coordinated by twelve oxygen atoms whilst iron is located in an octahedral array of oxygen (red spheres).…”
Section: Srfeo2fmentioning
confidence: 99%
See 1 more Smart Citation